2004
DOI: 10.1148/radiol.2312030606
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Breast Imaging: Average Tissue Property Values in Women with Negative Clinical Findings

Abstract: Representative data are provided for three electromagnetic breast imaging techniques-near-infrared spectroscopy, electrical impedance spectroscopy, and microwave imaging spectroscopy-to serve as potential benchmarks for future investigation. The breasts of 23 women without clinical or mammographic findings of disease were imaged in the coronal plane with nonionizing radiation of varying frequencies. Average electromagnetic property values were reconstructed at each frequency on the basis of computational model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 32 publications
2
75
3
Order By: Relevance
“…Adding alternative imaging modalities, particularly modalities providing functional assessment of tissues, to structural x-ray imaging could provide improvement for cancer diagnosis. In particular, functional imaging by means of diffuse optical tomography (DOT) has shown great promise in this respect (11)(12)(13)(14)(15)(16).…”
Section: Imaging Instrumentationmentioning
confidence: 99%
“…Adding alternative imaging modalities, particularly modalities providing functional assessment of tissues, to structural x-ray imaging could provide improvement for cancer diagnosis. In particular, functional imaging by means of diffuse optical tomography (DOT) has shown great promise in this respect (11)(12)(13)(14)(15)(16).…”
Section: Imaging Instrumentationmentioning
confidence: 99%
“…Recent studies have used scattering to study structural variations. For example, Poplack et al 38 showed in a normal cohort of 23 women that there is a significant decrease in the reduced scattering coefficient ͑ s Ј͒ at 785 nm with increasing body mass index and that adipose tissue was less scattering than glandular tissue, as expected. The same trend was observed by Durduran et al 29 in a subject pool of 52 volunteers.…”
Section: Discussionmentioning
confidence: 65%
“…Similar results were also reported 28 for a 3 days tumor inoculated rat with 1064 nm PAT system. On the other hand, since early tumor development is always accompanied by higher water content and induced larger local conductivity, 29 the tumor is notably detected in TAT image [ Fig. 2(c)].…”
Section: Resultsmentioning
confidence: 99%